2008
DOI: 10.2134/jeq2007.0438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Cover Data on Nitrous Oxide Inventory in Fen Meadows

Abstract: Landscape representations based on land cover databases differ significantly from the real landscape. Using a land cover database with high uncertainty as input for emission inventory analyses can cause propagation of systematic and random errors. The objective of this study was to analyze how different land cover representations introduce systematic errors into the results of regional N2O emission inventories. Surface areas of grassland, ditches, and ditch banks were estimated for two polders in the Dutch fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
1
32
0
1
Order By: Relevance
“…Jiao et al (2010) found that up to 18 % of the soil organic carbon in an agricultural landscape in the North China Plain was associated with built structures and the disturbed lands surrounding these structures, commonly ignored in large scale assessments. Nol et al (2008) found that nitrous oxide emissions were overestimated by about 10 % in case land cover data were used that ignored the presence of ditches in the landscape. For other indicators a potential problem of the commonly used representation of landscapes by the dominant land cover resides in the absence of a representation of the spatial structure and possibilities to account for spatial interactions that are so important for ecosystem functioning.…”
Section: Representation Of Landscapes In Global Environmental Assessmmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiao et al (2010) found that up to 18 % of the soil organic carbon in an agricultural landscape in the North China Plain was associated with built structures and the disturbed lands surrounding these structures, commonly ignored in large scale assessments. Nol et al (2008) found that nitrous oxide emissions were overestimated by about 10 % in case land cover data were used that ignored the presence of ditches in the landscape. For other indicators a potential problem of the commonly used representation of landscapes by the dominant land cover resides in the absence of a representation of the spatial structure and possibilities to account for spatial interactions that are so important for ecosystem functioning.…”
Section: Representation Of Landscapes In Global Environmental Assessmmentioning
confidence: 99%
“…The number of landscape pictures contributed by citizens worldwide available in georeferenced databases such as Panaramio indicates the potential of such an approach. Alternative approaches include the combination of broad-scale landscape typologies with more detailed case studies where the characteristics of the landscape composition and structure are described in more detail (Nol et al 2008;Ellis et al 2009). Next to making parameters of landscape structure available at the global scale, the second challenge would be to further develop models that actually use the data, taking into account the effect of these structures on e.g.…”
Section: Ways Forwardmentioning
confidence: 99%
“…De ce point de vue, CLUE-S et DINAMICA offrent le plus de potentiel avec d'autres outils (modèles, scénarios, logiciels, etc.) et la littérature en témoigne (Soares-Filho et al, 2006Nol et al, 2008 ;Schulp et al, 2008).…”
Section: Quantitésunclassified
“…Reclamation created a regular pattern of dikes, ditches and farmland (e.g. Bakker et al 1994;Nol et al 2008), of which the absolute level has been falling due to mineralisation of the peat. Comparable peatland polders have been reclaimed and drained around the world (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bakker et al 1994;Vermaat et al 2007Vermaat et al , 2008Nol et al 2008), or larger lakes due to subsequent erosion (Verhoeven 1992;Nieuwenhuis and Schokking 1997). The banks of these water bodies form a network of littoral transitions between land and water.…”
Section: Introductionmentioning
confidence: 99%